How Parents Can Help Kids Make Healthy Choices: Advice from Children (P04-006-19). (13th June 2019) - Eck, Kaitlyn; Delaney, Colleen; Byrd-Bredbenner, Carol; Shelnutt, Karla; Olfert, Melissa
Abstract: Objectives: To explore the advice school-age children would give parents to help their kids make good health-related behavioral choices (e.g., reducing sugary beverages, increasing fruits/vegetables, eating age-appropriate portions, having frequent family meals) and determine the congruence of children's advice with best-practice parenting guidelines. Methods: Children (6 to 11 years) from three states (FL, NJ and WV) participated in 1 of 65 semi-structured focus group discussions. Trained focus group moderators used a semi-structured script to ask children what advice they would give parents to help kids make healthy choices. Results: School-age children ( n = 195, 47% female) felt that parents played an important role in helping kids make healthy choices. Standard content analysis procedures indicated that some of the advice children would give parents was in line with best-practice parenting guidelines, such as telling kids about the benefits of healthy choices, encouraging kids to make healthy choices, planning ahead to make healthy choices possible, and establishing a routine and expectations for healthy choices. Children also advised parents to involve kids in planning and preparing meals, politely ask kids to help them, and teach kids how to cook. However, other advice children gave contradicted best-practice parenting guidelines. Children often advised parents to use rewards (e.g., money and highly palatable foods) as bribes to get kids to make healthy choices. They also frequently advised parents to punish kids for making unhealthy choices by taking away dessert or electronic devices or grounding them. Children commonly advised parents to "trick" kids into making healthy choices by mixing vegetables into other dishes to hide them or coloring water so kids think it is juice. Conclusions: Although some of the advice kids would give parents was in line with best-practice parenting guidelines, not all was. Kids' advice may suggest that their parents have utilized non-recommended strategies, which can negatively influence children's own eating behaviors now as well as the parenting practices these kids may use in the future. Thus, to protect future generations, nutrition interventions targeting children should consider incorporating best-practice parenting strategies related to healthy choices. Funding Sources: 2011–68, 001-30, 170 and 2017–680, 001-26, 351.